THE TEACHERS' CLINIC . - Beckert, Ralph F.; Gray, Otha L. (The Accounting Review, 1965)
Abstract Many forces both within and without the academic arena have focused attention in recent years upon the content and quality of American education. Over the years various education study committees of the American Accounting Association and the American Institute of Certified Public Accountants, as well as representatives of other interested groups, and individuals, have considered both the problems of total curriculum and content of specific courses in accounting education, of which taxation is traditionally a part. More recently the 1961 Committee on Income Tax Instruction of the American Accounting Association rendered a report embodying a statement of the recommended aims and objectives of income tax instruction. The survey revealed that in the opinion of 70 per cent of the responding professors the objective of the first course should be no different if students take a single course than if they take additional tax courses. A minority of 30 percent, however, favor an extended subject matter coverage and a broad approach to the first course, with a shifting of technique and professional emphasis to the second course when a two course sequence is typical for students.